Qur'ani literacy as the basis for the formation of Sakinah and justice families - Mukhrom Mukhrom; Hidayatullah Ismail (Priviet Social Sciences Journal, 2025)
This study aims to examine Qur'anic literacy as a conceptual and practical foundation for shaping sakinah (harmonious) and just families amid the challenges of modernity, value disruption, and global spiritual crises. Qur'anic literacy is understood not merely as the ability to read the sacred text, but as an internalization of divine values that cultivates moral, spiritual, and social awareness within Muslim family life. Employing a descriptive qualitative approach through library research, this study analyzes primary and secondary sources, including classical and contemporary tafsir, scholarly books, and scientific articles published in the past five years. Thematic analysis was used to explore Qur'anic principles relevant to the formation of harmonious and equitable family structures. The findings reveal that Qur'anic literacy serves as an epistemological foundation for developing ethical and egalitarian perspectives on spousal relationships and child-rearing. Families with a high level of Qur'anic literacy tend to maintain balanced roles, strengthen spiritual communication, and foster compassion-based dynamics within the household. Furthermore, integrating Qur'anic literacy with digital technology plays a significant role in reinforcing moral education and family resilience in the contemporary era. This study concludes that contextual and reflective Qur'anic literacy is crucial for building Muslim families that are not only harmonious and just but also serve as the cornerstone of Qur'anic civilization grounded in humanism, inclusivity, and social justice.